2014
DOI: 10.7227/jace.20.2.4
|View full text |Cite
|
Sign up to set email alerts
|

From Adults to Non-Traditional Students to Lifelong Learners in Higher Education: Changing Contexts and Perspectives

Abstract: This chapter looks into the changing contexts and definitions of clienteles of lifelong learners over the last quarter of a century. The author has been involved in three closely related studies on who lifelong learners are, how they access and participate in higher education (HE), and how and what are they learning in HE and summarises some of the developments and issues over the 25 years that these studies cover (approximately 1987 to 2012).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 8 publications
0
18
0
4
Order By: Relevance
“…Mature students have been a growing group of applicants to higher education for several decades (Evans & Nation, 1996;Pearce, 2017;Schuetze, 2014), although application numbers have fallen in recent years (UCAS, 2017). The Universities and Colleges Admissions Service (UCAS) (2017) found that in 2017, 10.4% of successful HE applicants from the UK were mature, and in 2018, the number of acceptances for students aged 26 and over increased by 6.7% (UCAS, 2018).…”
Section: Mature Studentsmentioning
confidence: 99%
“…Mature students have been a growing group of applicants to higher education for several decades (Evans & Nation, 1996;Pearce, 2017;Schuetze, 2014), although application numbers have fallen in recent years (UCAS, 2017). The Universities and Colleges Admissions Service (UCAS) (2017) found that in 2017, 10.4% of successful HE applicants from the UK were mature, and in 2018, the number of acceptances for students aged 26 and over increased by 6.7% (UCAS, 2018).…”
Section: Mature Studentsmentioning
confidence: 99%
“…Jejich rozhodování vstoupit na vysokou školu není termínováno, nemá vnější oporu 9 a na samotný proces rozhodování si musí potenciální student vyhradit čas během vytížení v pracovním i osobním životě. Schuetze (2014) upozorňuje, že netradiční studenti mohou být ohroženi již při samotném výběru školy kvůli špatné informovanosti, nižší schopnosti orientovat se v akademických standardech kvality a kvůli vlastním nerealistickým očekáváním. Mohou snadněji podlehnout nekorektním praktikám studijních nabídek a bez patřičné poradenské podpory je může jejich rozhodnutí přivést k méně vhodnému studiu.…”
Section: Specifika Netradičních Studentů Při Volbě Vysokoškolského Stunclassified
“…Pokud tedy Schuetze a Sloweyová (2002) či Twigg-Flesner (2018) formulují opatření, jimiž by vysoké školy měly netradičním studentům vycházet vstříc (modulové uspořádání kurikula, široká nabídka forem vzdělávání, e-learning, finanční, poradenská či mentorská podpora studentů), nejedná se ze strany vysokých škol o nějakou službu z milosti či nevratnou investici. Naopak, takové změny mohou mít pozitivní dopady nejen na studentskou obec (Schuetze, 2014), ale i na celkové prostředí vysokých škol.…”
Section: Závěr: Potenciál Netradičních Vysokoškolských Studentů Pro Tunclassified
See 1 more Smart Citation
“…Within the paradigm of lifelong learning, learners are at the forefront: more specifically, they all have varying backgrounds and learning paths that bring them (back) to universities as lifelong learners. (Schuetze, 2014;Schuetze & Slowey, 2012). Universities need to respond more flexibly to individual learners' needs and changing market requirements.…”
Section: Introductionmentioning
confidence: 99%